Long‐term opioid management for chronic noncancer pain - Noble, Meredith (Cochrane Database Syst Rev, 2010)
BACKGROUND: Opioid therapy for chronic noncancer pain (CNCP) is controversial due to concerns regarding long‐term effectiveness and safety, particularly the risk of tolerance, dependence, or abuse. OBJECTIVES: To assess safety, efficacy, and effectiveness of opioids taken long‐term for CNCP. SEARCH METHODS: We searched 10 bibliographic databases up to May 2009. SELECTION CRITERIA: We searched for studies that: collected efficacy data on participants after at least 6 months of treatment; were full‐text articles; did not include redundant data; were prospective; enrolled at least 10 participants; reported data of participants who had CNCP. Randomized controlled trials (RCTs) and pre‐post case‐series studies were included. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted safety and effectiveness data and settled discrepancies by consensus. We used random‐effects meta‐analysis' to summarize data where appropriate, used the I(2) statistic to quantify heterogeneity, and, where appropriate, explored heterogeneity using meta‐regression. Several sensitivity analyses were performed to test the robustness of the results. MAIN RESULTS: We reviewed 26 studies with 27 treatment groups that enrolled a total of 4893 participants. Twenty five of the studies were case series or uncontrolled long‐term trial continuations, the other was an RCT comparing two opioids. Opioids were administered orally (number of study treatments groups [abbreviated as "k"] = 12, n = 3040), transdermally (k = 5, n = 1628), or intrathecally (k = 10, n = 231). Many participants discontinued due to adverse effects (oral: 22.9% [95% confidence interval (CI): 15.3% to 32.8%]; transdermal: 12.1% [95% CI: 4.9% to 27.0%]; intrathecal: 8.9% [95% CI: 4.0% to 26.1%]); or insufficient pain relief (oral: 10.3% [95% CI: 7.6% to 13.9%]; intrathecal: 7.6% [95% CI: 3.7% to 14.8%]; transdermal: 5.8% [95% CI: 4.2% to 7.9%]). Signs of opioid addiction were reported in 0.27% of participants in the studies that reported that outcome. All three modes of administration were associated with clinically significant reductions in pain, but the amount of pain relief varied among studies. Findings regarding quality of life and functional status were inconclusive due to an insufficient quantity of evidence for oral administration studies and inconclusive statistical findings for transdermal and intrathecal administration studies. AUTHORS' CONCLUSIONS: Many patients discontinue long‐term opioid therapy (especially oral opioids) due to adverse events or insufficient pain relief; however, weak evidence suggests that patients who are able to continue opioids long‐term experience clinically significant pain relief. Whether quality of life or functioning improves is inconclusive. Many minor adverse events (like nausea and headache) occurred, but serious adverse events, including iatrogenic opioid addiction, were rare.